2021
DOI: 10.18280/acsm.450206
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermal Behavior of a Horizontal Two Fins Annular Tube Heat Exchanger with Melting Phase Change Material: Fins Orientation Effects

Abstract: This paper investigates the effect of fins orientations of a horizontal two fins annular tube heat exchanger on enhancing the heat transfer during the melting process of n-eicosane, as phase change material (PCM) used in thermal storage systems. Based on the enthalpy-porosity method, two-dimensional model is performed and solved by Ansys Fluent. The impact of the fins orientation on melting rate, thermal conduction and natural convection, as the angle of the system varied from 0º (vertical fins) to 90º (horizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Nesrine Boulaktout et al [1] conducted a numerical and practical study to improve the heat transfer of annular tube heat exchangers using fins to accelerate the melting rate of nicosan, which was examined in practice. The thermal potential energy of the porous material in nicosan was calculated and the phase type was changed, and it was found that the melting process of the material when changing the phase needs additional time .She also explained that the use of metal fins improves heat transfer and that changing their direction horizontally and vertically has an impact on thermal performance.…”
Section: Addition Of Annular Finsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesrine Boulaktout et al [1] conducted a numerical and practical study to improve the heat transfer of annular tube heat exchangers using fins to accelerate the melting rate of nicosan, which was examined in practice. The thermal potential energy of the porous material in nicosan was calculated and the phase type was changed, and it was found that the melting process of the material when changing the phase needs additional time .She also explained that the use of metal fins improves heat transfer and that changing their direction horizontally and vertically has an impact on thermal performance.…”
Section: Addition Of Annular Finsmentioning
confidence: 99%
“…Basically, there are three basic types of thermal energy storage systems, as shown in Figure 1, i.e. thermochemical energy storage units, perceptible thermal energy storage units, and potential thermal energy storage units [1]. The depletion of the ozone layer and the rise in fuel costs have encouraged researchers to improve the efficiency of systems based on sustainable energy sources such as energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…Yu 26 determined the optimal fin-splitting angle, while Zheng 27 determined that the optimal number of tree-like fin layers is 4 using the transient model enthalpy-porosity method. Notably, Boulaktout 28 and Chen 29 highlighted that heat conduction and heat transfer play a dominant role during the initial stage of PCM melting. The heat transfer at the fin level exhibits higher efficiency when the upper half of the PCM has melted, but it becomes less effective during the melting of the lower half of the PCM.…”
Section: Ring Finsmentioning
confidence: 99%
“…Notably, Boulaktout 28 and Chen 29 highlighted that heat conduction and heat transfer play a dominant role during the initial stage of PCM melting. The heat transfer at the fin level exhibits higher efficiency when the upper half of the PCM has melted, but it becomes less effective during the melting of the lower half of the PCM.…”
Section: Internal Structure To Enhance Heat Exchangementioning
confidence: 99%
“…Several active and passive methods, such as bubbles nuclei, 1 and ultrasonic vibrations, 2 have been used to manage water phase changes efficiently. Passive approaches such as inserting metallic fins, [3][4][5] nanoparticles, [6][7][8][9] and metal foam, 10,11 have been used to overcome PCM's limited heat conductivity. On the other hand, dispersion nanoparticles improve both the thermal conductivity and the subcooling impact of PCM water.…”
mentioning
confidence: 99%